306 Post-Hemorrhagic Stroke Scar Components in the Rat Intracerebral Hemorrhage Model. (April 2023) - Koduri, Sravanthi; Okauchi, Masanobu; Keep, Richard; Pandey, Aditya S.; Xi, Guohua
Abstract : INTRODUCTION: Intracerebral hemorrhage (ICH) has long been known to be a cause of significant morbidity and mortality with few medical or surgical treatment options. Though various studies have investigated hematoma evacuation and iron chelation in acute ICH management, there has been minimal study regarding the components of the scar cavity following ICH. METHODS: To investigate this further, our group injected 100 µL of autologous blood into the right basal ganglia of 18-month-old male Fisher 344 rats and euthanized the rats for histological brain analysis at 2 months following injection. RESULTS: Study of these brains revealed that the post-hemorrhagic scar cavity had increased fluorescence with GFAP, a marker of astrogliosis following injury, with a reduction in DARPP-32, a protein enriched in dopamine-innervated areas and involved with neurotransmission, which indicates neuronal loss. It was also noted that there was a statistically significant increase in Olig2+ oligodendrocyte cells within the scar cavity compared to similar regions in the contralateral hemisphere or in control animals. Interestingly, when stained with CC1, a marker of mature oligodendrocytes, the scar cavity contained a mix of both mature and precursor oligodendrocytes, indicating that this increase is likely proliferative in nature rather than due to a migration phenomenon. CONCLUSIONS: The role of these Olig2+ cells, how they are affected by deferoxamine administration and whether they are functional and contributing to the recovery of this injured region is currently under investigation. As oligodendrocytes provide support and insulation to the axons of the central nervous system, this proliferation within the scar cavity may indicate a form of healing and be the first understanding of the delayed recovery that takes placed after ICH.